Optimization model for power generation using thermoelectric generator. (February 2019) - Rana, Sohel; Date, Abhijit; Iqbal, Arbab; Akbarzadeh, Aliakbar
Abstract: In this work, optimization model has been developed to simulate TEG (Thermoelectric generator) based power generation system. Proposed model able to predict the gross power, net power and pumping power for all operating conditions and heat exchanger dimensions. Model also able to choose the optimum operating conditions, dimensions of heat exchanger to obtained maximum net power. TEG module has been chosen from the commercially available modules with efficiency of 1.91% for the targeted low-grade waste heat temperature of Th =90 o C and Tc =15 o C. Predicted maximum net power was 79.02 W from 50 TEG modules and optimum operating conditions were 300 L/min mass flow rate, exchanger dimensions are 0.08 m length, 1 m width and 4 mm gap size.